Production and Financial Management Training to Increase Micro-Business Productivity in Rural Areas - Bella Suci Novitri1; Walla Astianty Putri; Joko Rianto (LPPM Akademi Teknik Adikarya, 2025)
Micro-enterprises in rural areas play a vital role in supporting the local economy, yet they still face various challenges in production and financial management, resulting in low productivity. This community service program aims to enhance the capacity of micro-enterprises through production and financial management training to encourage increased productivity and business sustainability in rural areas. The program implemented a participatory approach, encompassing partner needs identification, production management training, financial record keeping, and direct mentoring for implementing business management within participating businesses. The training materials covered production planning, product quality control, raw material efficiency, production cost recording, and the preparation of simple financial reports. The results demonstrated an increase in participants' understanding of how to plan production processes more efficiently and their ability to systematically record their business finances. Furthermore, entrepreneurs began to be able to control production costs and improve product quality, resulting in increased production volume and revenue. This program also fostered awareness among entrepreneurs about the importance of professional business management to maintain business sustainability amidst increasingly competitive markets. Thus, production and financial management training is an effective strategy for increasing the productivity of rural micro-enterprises while strengthening the local economy. It is recommended that this program be continued through ongoing mentoring to ensure consistent implementation of business management practices.